Saints, scholars and the idealized past in Philippine Muslim separatism - McKenna, Tom (The Pacific review, 2002)
(...) The Muslim separatist movement that began in 1968 had dual goals. It was primarily an ethno-nationalist endeavour that had as its primary goal the creation of a Philippine Muslim nation - a nation-state governed by Philippine Muslims and modelled on the sultanates of the precolonial period. The second goal of the Muslim separatist movement was to reform local religious and cultural practices under the leadership of a new set of religious leaders. To understand the place of atavism and puritanism in the Philippine Muslim separatist movement The author review the largely local tradition of saints and the more universal Muslim institution of religious scholars as they have interacted in the contemporary Muslim Philippines. He conciders contradictions between revanchist and reformatist goals of the movement.(...) (Pac Rev/DÜI)